1991
DOI: 10.1056/nejm199108153250702
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Hepatitis C Virus by Organ Transplantation

Abstract: Organ transplantation can transmit hepatitis C. This raises serious questions about the continued acceptance of organs from donors positive for anti-HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(109 citation statements)
references
References 34 publications
3
105
0
1
Order By: Relevance
“…The initial report of Laquaglia et al [16] found marked extrahepatic infections in hepatitis-positive post-transplant patients. A higher incidence of infection and death due to sepsis was also reported by Periera et al [4] and recently by Rao and Ma [17,] who found a higher incidence of infection in HCV-positive patients as compared to the HCV-negative counterparts. In the present study, the number of patients who developed diabetes in the presence of immunosuppressive medication (cyclosporine and prednisolone) were found more in HCV-positive patients than in HCV-negative patients.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The initial report of Laquaglia et al [16] found marked extrahepatic infections in hepatitis-positive post-transplant patients. A higher incidence of infection and death due to sepsis was also reported by Periera et al [4] and recently by Rao and Ma [17,] who found a higher incidence of infection in HCV-positive patients as compared to the HCV-negative counterparts. In the present study, the number of patients who developed diabetes in the presence of immunosuppressive medication (cyclosporine and prednisolone) were found more in HCV-positive patients than in HCV-negative patients.…”
Section: Discussionsupporting
confidence: 49%
“…Pereira et al [4] found a relatively higher risk of graft loss, death and sepsis in HCV-positive transplant patients than HCV-negative patients. In line with this report, the present study established a higher incidence of graft failure and fatal infections (table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this confusion may have arisen from the methods of detection of HCY positivity, which in many early studies relied on a first generation assay with a significant false-positive rate. Pereira et al 19 showed that 75% of seropositive donors transmitted HCY to the transplant recipient. In contrast.…”
Section: The Donor With Hepatitis Cmentioning
confidence: 99%
“…This prevalence may be as high as 6 % in some regions of Africa and the Middle East (Darwish et al, 1993). Since HCV is mainly transmitted via blood, haemo-derivatives and haemodialysis, the main populations at risk are drug addicts, the recipients of blood transfusions and of haemodialysis (Alter, 1989), organ transplants (Pereira et al, 1991) and tattoos (Ko et al, 1992) and health-care personnel (Polish et al, 1993). Approximately 80 % of patients suffering from acute hepatitis C develop chronic hepatitis (Lau et al, 1993) and 20-35 % develop liver cirrhosis (Alter, 1989).…”
Section: Introductionmentioning
confidence: 99%